Methicillin-Resistant Staphylococcus aureus ST398 in Swine Farm Personnel, Belgium - Denis, Olivier (Centers for Disease Control and Prevention, 2009)
We assessed methicillin-resistant Staphylococcus aureus (MRSA) in persons on 49 swine farms in Belgium. Surveys showed that 48 (37.8%) persons carried MRSA ST398 and 1 (0.8%) had concurrent skin infection. Risk factors for carriage were MRSA carriage by pigs, regular contact with pigs and companion animals, and use of protective clothing.